ElastoCaloric (eC) Cooling: recent studies and preliminary results on materials and devices. Issue 1 (1st April 2022) - Cirillo, Luca; Farina, Adriana Rosaria; Greco, Adriana; Masselli, Claudia
Abstract: Refrigeration is a process aimed at lowering the temperature of an environment compared to the outside temperature. It has always played a fundamental role in modern industry: food, for the preservation of food; in the air conditioning of buildings, to make them habitable and even in the field of medicine and biology, for the preservation of samples and particular therapies. Today refrigeration systems, are responsible for about 17% of the world's electricity consumption. Therefore, the scientific community is researching solid-state refrigeration, which is 50% more efficient than vapour compression systems. Solid-state refrigeration is based on some materials' caloric effect, which can release or absorb latent heat when subjected to an external field (magnetic, electric, pressure or strain) release. Elastocaloric Refrigeration is one of the most minor explored frontiers, unlike magnetocaloric and electro-caloric systems. Some preliminary studies confirm that the eC systems have the advantage of being able to decrease the intensity of the external field (with a relative increase of the COP). In this work, a review on Ec systems is carried out, with particular attention to the description of the properties of the materials used, the various types of stress application. The results have been presented in terms of temperature, entropy, latent heat and COP.